The Characteristics of Liquid Soap with Varied Additions of Moringa Leaf Extract (Moringa Oleifera L.) - Andrew Setiawan Rusdianto; Fillyvio Nizhomia; Giyarto Giyarto; Andi Eko Wiyono (Food, Agriculture and Natural Resources - NETWORKS, 2022)
Liquid soap is a cleaning product, which works by reacting to oil or fat and alkaline potassium hydroxide. This principle is also known as a saponification reaction. Soap works for cleaning and acts as an antibacterial component. Moringa leaves contain phytochemical compounds that can inhibit the growth of bacteria so it enhances soap production. The inhibitory power of Moringa leaf extract is determined by its concentration in liquid soap. The variations of Moringa leaf extract in liquid soap can affect the characteristics of resultant liquid soap. The purpose of this study was to determine the effect of varied additions of Moringa leaf extract on the characteristics of liquid soap and to determine the addition of Moringa leaf extract, which produces liquid soap that meets SNI requirements and has good antibacterial power.This research involved laboratory experiment using quantitative descriptive analysis. The study was conducted using a factorial completely randomized design, with one factor, namely varied additions of Moringa leaf extract consisting of 3%, 5%, and 7% extract relative to the weight of the base soap. The results has showed that different concentrations of Moringa leaf extract has a significant effect on antibacterial activity, free alkali levels, specific gravity, viscosity, and foaming power of liquid soap. The resultant liquid soap has satisfied SNI 06-4085-2017. The results of organoleptic test by assessing consumer preferences demonstrate the highest score in sample A1 (soap with 3% Moringa leaf extract). The best liquid soap formulation treatment is A3 (liquid soap formulation 7% Moringa leaf extract) with antibacterial power (zone of inhibition) of 17 mm, pH 10.23, free alkali content 0.026%, specific gravity 1.040 g/ml, viscosity 2.06 Cps, and 4.8 cm foam power.